What remains of the human in the Anthropocene? Living between ‘nature’ and ‘culture’ in the posthuman condition - Henry, Barbara (Itinerari, 2023)
In this contribution, I aim to develop a philosophical account of ‘posthuman’ that enables us to conceive a future society of humanoids, humans, hybrids, artificial beings, who are free and equal. This analysis will help me to answer the paradoxical question: what does it means to be human in the Anthropocene (the era of the Anthropos). This expression – ‘posthuman’ or ‘posthuman condition’ is to be understood as referring to symbols and phenomena different from those associated with ‘transhuman’. (Critical) Posthumanism is the corresponding line of thought, necessary for the paradigm shift we are in need of. According to this, posthuman is to be interpreted here as material, not anthropocentric, but rather interspecist, osmotic and relational, a horizon of effective sharing of experiences, dangers and challenges. In contrast, ‘transhuman’ (as the transhumanist ideal movement is advocating with strong mediatic influence) is meant to refer to the ultimate transcending of humans into the pure ether of an ‘ideal’, immaterial network made up only of software, and lacking in relations with any material beings in the ecosystem or cosmos.